2018
DOI: 10.5005/jp-journals-10024-2424
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extra Root Canal Orifices of Maxillary First Permanent Molars in a Saudi Subpopulation Utilizing Microcomputed Tomography

Abstract: Aim:To study the prevalence of additional root canal orifices of upper first permanent molars in Saudi subpopulation in Jeddah, Kingdom of Saudi Arabia, utilizing micro-computed tomography X-ray (micro-CT). Materials and methods:One hundred extracted upper first permanent molars of Saudi patients were included in the study. Micro-CT was used to detect the prevalence of extra root canal orifices of the permanent upper first molars. Results:The evaluation of three-dimensional (3D) images of this study showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“… Study concluded that Saudi subpopulation had complex root anatomy of second maxillary premolars. [ 90 ] El Ashiry, E.A. and N.M. Farsi 2018 100 Maxillary first molars SkyScan micro-CT scanner (SkyScan 1172, SkyScan, Bruker, Belgium) 13.4 μm (SkyScan 1172, SkyScan, Bruker, Belgium) Disinfection of all the molars was done by sodium hypochlorite (5.25%), then placed in normal saline for 24 h then micro-CT was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Study concluded that Saudi subpopulation had complex root anatomy of second maxillary premolars. [ 90 ] El Ashiry, E.A. and N.M. Farsi 2018 100 Maxillary first molars SkyScan micro-CT scanner (SkyScan 1172, SkyScan, Bruker, Belgium) 13.4 μm (SkyScan 1172, SkyScan, Bruker, Belgium) Disinfection of all the molars was done by sodium hypochlorite (5.25%), then placed in normal saline for 24 h then micro-CT was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Another micro-CT study included in this systematic review was conducted on maxillary first molars to detect extra root canal orifices which is usually difficult due to dentin ledge that can cover the floor of pulp chamber [ 90 ]. Commonly it is approved that maxillary first molars have three or four pulp canals, but using 3D images by micro-CT this study evaluated the presence of three (7.01%), four (47.37%), five (35.09%) and six (10.53%) pulp canal orifices [ 90 ].…”
Section: Discussionmentioning
confidence: 99%